Exposure routes and health effects of microcystins on animals and humans: A mini-review. (1st September 2018) - Massey, Isaac Yaw; Yang, Fei; Ding, Zhen; Yang, Shu; Guo, Jian; Tezi, Clara; Al-Osman, Muwaffak; Kamegni, Robert Boukem; Zeng, Weiming
Abstract: Microcystins (MCs) pollution has quickly risen in infamy and has become a major problem to public health worldwide. MCs are a group of monocyclic hepatotoxic peptides, which are produced by some bloom-forming cyanobacteria in water. More than 100 different MCs variants posing a great threat to animals and humans due to their potential carcinogenicity have been reported. To reduce MCs risks, the World Health Organization has set a provisional guideline of 1 μg/L MCs in human's drinking water. This paper provides an overview of exposure routes of MCs into the human system and health effects on different organs after MCs exposure including the liver, intestine, brain, kidney, lung, heart and reproductive system. In addition, some evidences on human poisoning and deaths associated with MCs exposure are presented. Finally, in order to protect human life against the health threats posed by MCs, this paper also suggests some directions for future research that can advance MCs control and minimize human exposure to MCs.